Borophene Embedded Cellulose Paper for Enhanced Photothermal Water Evaporation and Prompt Bacterial Killing. Issue 7 (25th January 2023) - Guan, Xinwei; Kumar, Prashant; Li, Zhixuan; Tran, Thi Kim Anh; Chahal, Sumit; Lei, Zhihao; Huang, Chien‐Yu; Lin, Chun‐Ho; Huang, Jing‐Kai; Hu, Long; Chang, Yuan‐Chih; Wang, Li; et al.
Abstract: Solar‐driven photothermal water evaporation is considered an elegant and sustainable technology for freshwater production. The existing systems, however, often suffer from poor stability and biofouling issues, which severely hamper their prospects in practical applications. Conventionally, photothermal materials are deposited on the membrane supports via vacuum‐assisted filtration or dip‐coating methods. Nevertheless, the weak inherent material‐membrane interactions frequently lead to poor durability, and the photothermal material layer can be easily peeled off from the hosting substrates or partially dissolved when immersed in water. In the present article, the discovery of the incorporation of borophene into cellulose nanofibers (CNF), enabling excellent environmental stability with a high light‐to‐heat conversion efficiency of 91.5% and water evaporation rate of 1.45 kg m −2 h −1 under simulated sunlight is reported. It is also demonstrated that borophene papers can be employed as an excellent active photothermal material for eliminating almost 100% of both gram‐positive and gram‐negative bacteria within 20 min under three sun irradiations. The result opens a new direction for the design of borophene‐based papers with unique photothermal properties which can be used for the effective treatment of a wide range of wastewaters. Abstract : A novel borophene‐embedded cellulose paper is fabricated by incorporating two‐dimensional borophene nanosheets inside the cellulose fiber structure. The borophene paper exhibits outstanding absorption properties, featuring excellent stability and mechanical properties for photothermal water evaporation and bacterial killing applications.